Manual on Scientific Communication for Postgraduate Students and Young Researchers in Technical, Natural and Life Sciences - Van Cleemput, Oswald; Saso, Luciano (IntechOpen, 2017)
The "Manual on Scientific Communication for Postgraduate Students and Young Researchers in Technical, Natural, and Life Sciences" is meant to be a practical guide for the preparation of theses, papers, posters, and other scientific documents. Upon going through the different chapters, the readers should be able to critically search for relevant literature; to correctly define and execute a research topic or project; to correctly write a scientific document; to know the characteristics of the different parts of a MSc degree or PhD degree thesis and a scientific paper; to correctly interpret publishing ethically sensitive material; to understand problems about falsification, fabrication of data, plagiarism, and ranking of authors; and to prepare and present a good poster.